On the Validity of Purchasing Power Parity: The Case of Sierra Leone - JABBIE, Mohamed; JACKSON, Emerson Abraham (Journal of Advanced Studies in Finance; Vol 11 No 1 (2020): JASF Volume XI Issue 1(21) Summer 2020DO - 10.14505//jasf.v11.1(21).03, 2020)
This paper attempts to empirically validate the Purchasing Power Parity (PPP) theory in the context of Sierra Leone. To achieve this objective, cointegration and error correction techniques were utilized to account for both long and short-run dynamics over the period 2007Q1 to 2019Q1. The Engel-Granger cointegration technique was utilized to ascertain the long-run relationship between the exchange rate and the price differential between Sierra Leone and the United States of America, while the redundant variable test was used to attain the parsimonious short-run error correction model. The results indicated a cointegrating relationship, while the coefficient on the price differential was greater than one (1), reflecting that the PPP does not hold for Sierra Leone. Moreover, the short-run results showed a rejection of the theory and rather endorses the presence of depreciation inertia, where past depreciation of the exchange rate is a major determinant of its current depreciating trend.